2004
DOI: 10.1007/bf02894252
|View full text |Cite
|
Sign up to set email alerts
|

Faecal fat content in healthy adults by the ‘acid steatocrit method’

Abstract: Malabsorption syndromes causing steatorrhoea are quite common in India. Estimation of faecal fat is an important non-invasive investigation, which provides vital information regarding the occurrence of malabsorption. The aim of this study was to estimate the fat excretion per day in stools of apparently healthy adults on an unrestricted diet in random spot stool samples using the Acid Steatocrit Method, which provides an alternate, simpler and yet reliable method of stool fat estimation. Several studies have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…It is well established that excess dietary fat can be excreted in faeces (steatorrhea) as the result of certain medical cases (malabsorption, exocrine pancreatic insufficiency, pancreatitis and so on). However, even in healthy individuals the amount of fat in faeces can vary between 5.8-12.4 g per day for adults [63]. Furthermore, Lorenzen and Astrup [64] have shown that a diet rich in dairy calcium (1977 mg per 10 MJ) increased faecal excretion of fat by up to 30% compared with diet low in calcium (504 mg per 10 MJ).…”
Section: The Missed Opportunity: Faeces Analysismentioning
confidence: 98%
“…It is well established that excess dietary fat can be excreted in faeces (steatorrhea) as the result of certain medical cases (malabsorption, exocrine pancreatic insufficiency, pancreatitis and so on). However, even in healthy individuals the amount of fat in faeces can vary between 5.8-12.4 g per day for adults [63]. Furthermore, Lorenzen and Astrup [64] have shown that a diet rich in dairy calcium (1977 mg per 10 MJ) increased faecal excretion of fat by up to 30% compared with diet low in calcium (504 mg per 10 MJ).…”
Section: The Missed Opportunity: Faeces Analysismentioning
confidence: 98%
“…The following formula was used to calculate acid steatocrit (%) = FL/(FL + SL) × 100, where FL is the fatty layer and SL the solid layer. The fat content was quantified as given by Bijoor et al …”
Section: Methodsmentioning
confidence: 99%
“…500-μL aliquot of the homogenized stool were added with 100 mL of Perchloric acid and the pH was confirmed to be < 1. The mixture was aspirated into a capillary tube, sealed at one end and centrifuged at 13000 revolutions per minute for exactly 15 min[ 9 , 11 ]. The length of the fatty layer and the length of the solid layer were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Acid steatocrit (%) was obtained by the formula: fatty layer/(fatty layer + solid layer) × 100. The stool fat (in grams/day) was calculated by the equation: -0.43 + (0.45 × acid steatocrit %)[ 9 ]. Steatorrhoea was diagnosed when the stool fat excretion was 7 g/d or higher[ 4 ].…”
Section: Methodsmentioning
confidence: 99%